Analis Peran dan Tugas Kader Posyandu dalam Pelaksanaan Program Pencegahan Stunting di Wilayah Kerja Puskesmas Perumnas - Sutan M. Siboro; Tionida Siboro; Hermawati P.; Ibnu Jafar; Tatin Wahyanto; Sondang Sidabutar (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Stunting is a persistent nutritional issue that affects children's physical growth and cognitive development, and its prevalence in Indonesia continues to be a major barrier to public health progress. Posyandu cadres, as the frontline of community health services, play a vital role in implementing stunting prevention programs. This study aims to explore the roles and responsibilities of Posyandu cadres in providing supplementary nutrition, promoting exclusive breastfeeding and complementary feeding (MP-ASI), monitoring infant growth and development, and assisting families in maintaining environmental sanitation. A qualitative descriptive approach using a case study technique was employed within the jurisdiction of Puskesmas Perumnas. The results show that cadres actively identify children at risk of stunting, offer nutritional education, and monitor growth, although they face challenges related to capacity, logistics, and coordination between sectors. To enhance the effectiveness of stunting prevention efforts, it is recommended that cadre capacity be strengthened through continuous training and supervision.